Achilles insertion bone pathology not related to pain in a triathlete with cystic fibrosis. Issue 8 (14th August 2018) - Welford, Paul; Alfredson, Håkan
Abstract: This report concerns the unusual case of a 48-year old, world-class triathlete who has won 11 ironman competitions. She has reached the top level of international endurance sport in spite of being diagnosed with cystic fibrosis. This patient presented with Achilles pain and severe bony pathology at her left Achilles insertion. Traditionally this condition is treated via tendon detachment and re-attachment or intra-tendinous surgery, followed by a protracted rehabilitation. These procedures were considered risky due to this patient's chronic disease with vulnerability to immobilization. Instead, she was treated by surgical removal of the superficial bursa alone, under local anaesthetic. This allowed the patient to become active and load her Achilles tendon immediately, and resulted in a significant symptomatic improvement. This case illustrates that despite the presence of severe tendon and bone pathology at the Achilles insertion, pain may originate in the superficial bursa; a structure ignored by traditional operations.